Chile : Report on Observance of Standards and Codes-Fiscal Transparency. (IMF Staff Country Reports; Country Report ;, 2003)
The Chilean government has succeeded in constructing and disseminating a clear view of its objectives and targets, both at the macroeconomic level and for individual budget programs. Government accountability to congress and the public is demonstrably being strengthened. A general reform challenge for Chile will be to institutionalize the many recent advances in transparency, so that they become permanent components of fiscal management. The flexibility inherent in such instruments as protocols and time-bound laws may contribute importantly to speedy and effective policy responses.